Analysis and Improvement of the Management of IT Projects - Díaz Piraquive, Flor Nancy; González-Crespo, Rubén; Medina García, Víctor Hugo (IEEE Latin America Transactions, 2017)
This paper shows the most usual causes on the failure cases in IT Project Management. There were evaluated different projects that finished without success. After the evaluation and the opinion of several researchers in the area, it got the main idea to get success, the capabilities of the project leader in management and leadership. Beside these ideas, there are other reasons why a project would be not completed successfully on time, cost or scope, here are detailed and a possible solution to avoid those problems. All the information collected is quantitative, because the percentage of projects that fails was calculated and why it happens. At the end of this contribution there are presented recommendations to improve the quality in the project management such as, schedule, control, tracking, and so on.
Casos de Fracaso en la Gestión de Proyectos TI
Keywords: project IT management; management and methodology; internal politics; control metrics and indicators; data collection failure; JCR; Scopus